Coatings to Improve Optoelectronic Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This selection is focused on coatings and films with applications in optoelectronics, such as photovoltaics, photocatalysis, and light-based sensors and phenomena. The studies investigate the optimal composition, crystalline structure, and morphology to deliver the different functionalities sought. Obtaining transparent p-type electrodes is challenging but extremely relevant in optoelectronics. Electric conduction mechanisms and the correlations with structure and doping are discussed. The important issue of the degradation pathways in perovskite-based solar cells and the possibilities offered by different types of coatings to encapsulate the devices as well as the beneficial effect of silica coating as an antireflection and antisoiling layer on well-established solar cells are discussed. New designs of nanoplasmonic films for chemical and biological molecule sensing are reviewed, such as the combination of metallic nanoparticles and nanostructured semiconductors and dispersing metallic or bi-metallic nanoparticles in CuO films. The impacts of structure, defects, and morphology on the photoactivated properties of WO3 films and on the shape memory behavior in Cu-Al-Ni thin films are discussed. Aggregated TiO2 nanoparticles on TiO2 layers are shown to enhance optical transmittance and confer a superhydrophilic characteristic. Finally, aspects of the fundamental characterization of thin films, Drude damping in thin films, and laser-induced deflection technique are discussed.